From science to arts, IDNLearn.com has the answers to all your questions. Discover prompt and accurate answers from our community of experienced professionals.
Sagot :
To prove that the statement is true for all natural numbers [tex]\(n\)[/tex] by mathematical induction, we follow these steps:
### Step 1: Prove the Base Case
First, we need to show that the statement is true for the initial value [tex]\(n = 1\)[/tex].
1. When [tex]\(n = 1\)[/tex], let's denote the number of dots at this step as [tex]\(d(1)\)[/tex].
2. According to the problem, we assume the initial configuration is true.
3. Thus, we have [tex]\(d(1) = d(0) + 1\)[/tex] since the total number of dots increases by 1 each time.
### Step 2: Assume the Statement is True for [tex]\(n = k\)[/tex]
Next, we assume the statement holds for some arbitrary natural number [tex]\(k\)[/tex]. This means we assume:
[tex]\[ P(k) = d(k), \][/tex]
where [tex]\(d(k)\)[/tex] denotes the number of dots at step [tex]\(k\)[/tex].
### Step 3: Prove that the Statement is True for [tex]\(n = k+1\)[/tex]
Given the hint that the total number of dots increases by [tex]\(n\)[/tex] each time, at step [tex]\(k + 1\)[/tex] the number of dots should be given by:
[tex]\[ d(k + 1) = d(k) + (k + 1). \][/tex]
Since we assumed the statement is true for [tex]\(n = k\)[/tex], we can write:
[tex]\[ P(k) = d(k). \][/tex]
Adding [tex]\((k + 1)\)[/tex] to both sides of this equation, we get:
[tex]\[ P(k) + (k + 1) = d(k) + (k + 1). \][/tex]
Since by definition ([tex]\( d(k + 1) = d(k) + (k + 1) \)[/tex]), we can substitute [tex]\(d(k + 1)\)[/tex] into the equation:
[tex]\[ d(k + 1) = d(k) + (k + 1). \][/tex]
Therefore, it follows that:
[tex]\[ P(k) + (k + 1) = d(k + 1). \][/tex]
By recognizing that [tex]\(P(k) + (k + 1)\)[/tex] can be viewed as [tex]\(P(k + 1)\)[/tex], we conclude that:
[tex]\[ P(k + 1) = d(k + 1). \][/tex]
This completes the proof by mathematical induction. We have shown that if the statement is true for [tex]\(n = k\)[/tex], then it is also true for [tex]\(n = k+1\)[/tex]. Thus, by the principle of mathematical induction, we can conclude that the statement is true for all natural numbers [tex]\(n\)[/tex].
### Conclusion
We have successfully used mathematical induction to prove that the statement is true for all natural numbers [tex]\(n\)[/tex]:
[tex]\[ \text{Proof Complete: If the statement is true for } n = k, \text{ it must also be true for } n = k + 1, \text{ thus completing the proof by induction.} \][/tex]
### Step 1: Prove the Base Case
First, we need to show that the statement is true for the initial value [tex]\(n = 1\)[/tex].
1. When [tex]\(n = 1\)[/tex], let's denote the number of dots at this step as [tex]\(d(1)\)[/tex].
2. According to the problem, we assume the initial configuration is true.
3. Thus, we have [tex]\(d(1) = d(0) + 1\)[/tex] since the total number of dots increases by 1 each time.
### Step 2: Assume the Statement is True for [tex]\(n = k\)[/tex]
Next, we assume the statement holds for some arbitrary natural number [tex]\(k\)[/tex]. This means we assume:
[tex]\[ P(k) = d(k), \][/tex]
where [tex]\(d(k)\)[/tex] denotes the number of dots at step [tex]\(k\)[/tex].
### Step 3: Prove that the Statement is True for [tex]\(n = k+1\)[/tex]
Given the hint that the total number of dots increases by [tex]\(n\)[/tex] each time, at step [tex]\(k + 1\)[/tex] the number of dots should be given by:
[tex]\[ d(k + 1) = d(k) + (k + 1). \][/tex]
Since we assumed the statement is true for [tex]\(n = k\)[/tex], we can write:
[tex]\[ P(k) = d(k). \][/tex]
Adding [tex]\((k + 1)\)[/tex] to both sides of this equation, we get:
[tex]\[ P(k) + (k + 1) = d(k) + (k + 1). \][/tex]
Since by definition ([tex]\( d(k + 1) = d(k) + (k + 1) \)[/tex]), we can substitute [tex]\(d(k + 1)\)[/tex] into the equation:
[tex]\[ d(k + 1) = d(k) + (k + 1). \][/tex]
Therefore, it follows that:
[tex]\[ P(k) + (k + 1) = d(k + 1). \][/tex]
By recognizing that [tex]\(P(k) + (k + 1)\)[/tex] can be viewed as [tex]\(P(k + 1)\)[/tex], we conclude that:
[tex]\[ P(k + 1) = d(k + 1). \][/tex]
This completes the proof by mathematical induction. We have shown that if the statement is true for [tex]\(n = k\)[/tex], then it is also true for [tex]\(n = k+1\)[/tex]. Thus, by the principle of mathematical induction, we can conclude that the statement is true for all natural numbers [tex]\(n\)[/tex].
### Conclusion
We have successfully used mathematical induction to prove that the statement is true for all natural numbers [tex]\(n\)[/tex]:
[tex]\[ \text{Proof Complete: If the statement is true for } n = k, \text{ it must also be true for } n = k + 1, \text{ thus completing the proof by induction.} \][/tex]
Thank you for being part of this discussion. Keep exploring, asking questions, and sharing your insights with the community. Together, we can find the best solutions. Thanks for visiting IDNLearn.com. We’re dedicated to providing clear answers, so visit us again for more helpful information.